Diagnosis of Mineral Deficiencies in Pinus patula Seedlings - Kaul, O. N.; Gupta, A. C.; Negi, J. D. S. (Indian Forester, 1974)
The paper describes the morphological symptoms caused by the deficiency of some macro-nutrients on Pinus potula seedlings and their effect on growth and dry matter production. Recognisable symptoms were caused by the deficiency of nitrogen, phosphorus, potassium and sulphur and this was reflected 10 height increment and dry matter production of the seedlings.